Corporate boards, interorganizational ties and profitability: the case of Japan - Matthias Raddant; Hiroshi Takahashi (Empirical Economics, 2021)
We analyze the ties between 4000 Japanese corporations in the time period from 2004 until 2013. We combine data about the board composition with ownership relationships and indicators of corporate profitability. The board network exhibits some clustering, which can partly be explained by ownership relations, and a tendency to form ties to other corporations from the same sector. Connectivity in the board network (corporate board interlocks) and ownership network (shareholdings) does have an influence profitability. Firms that are linked to peers with above average profitability are more profitable than firms in other relationships. Hence, network effects partly explain why board interlocks and ownership ties are not always beneficial.
Keywords: L25; G32; M12; C55; 330; Corporate board interlock; Firm performance; Firm networks; Executive survival